Effect of Chemical Reaction on Heat and Mass transfer of Porous MHD Casson Nano Fluid with Melting and Joule heating - Yuvaraju, Namala; Hymavathi, Dyapa (Zielona Góra: Uniwersytet Zielonogórski)
The purpose of this study is to use computational tools to evaluate the effects of Joule heating, chemical reactions and melting on heat and mass transfer of a non-Newtonian Casson nano fluid flow across a porous stretched surface. The governing equations containing partial derivatives are consistent with nonlinear ordinary differential equations. The transformations are subject to the similarity variable, which is employed in the equations` solution. To generate approximate answers, a numerical method based on the Shoot technique and the Runge-Kutta method is used.
Keywords: Casson nano fluid; chemical reaction; melting; Joule heating; stretching surface